SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PROGRAM STUDI DI STMIK NEUMANN DENGAN METODE FUZZY LOGIC - Denny HS Maha; Yeremia Okta Ginting (UPPM, 2016)
Often one of the students in choosing courses that are not in accordance with her wishes. So the selection of decision support systems courses need to be made to make it easier for prospective students in choosing majors wanted. Most of the data they collect only the data in the form of guidance or studies must take a test try out. This research will be designed a decision support system for selecting a course. The method I use in the design of this system is the method of Fuzzy Logic. This system can display the results in a study program in accordance with the required criteria. This app is designed using VB Net. From the results of testing this system in the data entered will be processed in accordance with the criteria that have been provided by the system. The output of this system shows the most suitable program terhahap wantid prospective students who enroll in STMIK Neumann.